(untitled) (Nóema, 2021)
The evolution of language represents one of the main complex systems investigated by different scientific domains and philosophy. The phylogeny of the trait is analyzable from different perspectives, which make evident its weaved and multilayered nature. In the present essay it is presented the dialogue between some researchers from different disciplines who propose original views regarding the analysis of the evolutionary perspective, in an inclusive and hybrid horizon. Secondly, it is exposed the theoretical frontier which identifies in language not only a decisive feature in social contexts, but also an environment itself.